2005
DOI: 10.1128/jb.187.22.7845-7852.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Sigma Factor RpoS Is Required for the In Vivo-Specific Repression ofBorrelia burgdorferiPlasmid lp54-BorneospAandlp6.6Genes

Abstract: While numerous positively regulated loci have been characterized during the enzootic cycle of Borrelia burgdorferi, very little is known about the mechanism(s) involved in the repression of borrelial loci either during tick feeding or within the mammalian host. Here, we report that the alternative sigma factor RpoS is required for the in vivo-specific repression of at least two RpoD-dependent B. burgdorferi loci, ospA and lp6.6. The downregulation of ospA and Ip6.6 appears to require either a repressor molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
156
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(160 citation statements)
references
References 72 publications
4
156
0
Order By: Relevance
“…Earlier studies have shown that bba62, which encodes the Lp6.6 lipoprotein, is strongly downregulated in an RpoS-dependent manner when B. burgdorferi is cultivated in DMCs implanted into the peritoneal cavities of rats (i.e. under mammalian infection-like conditions) (Caimano et al, 2005(Caimano et al, , 2007. In agreement with these findings, bba62 was downregulated in B. burgdorferi by RpoS in our study, even under in vitro culture conditions.…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
See 3 more Smart Citations
“…Earlier studies have shown that bba62, which encodes the Lp6.6 lipoprotein, is strongly downregulated in an RpoS-dependent manner when B. burgdorferi is cultivated in DMCs implanted into the peritoneal cavities of rats (i.e. under mammalian infection-like conditions) (Caimano et al, 2005(Caimano et al, , 2007. In agreement with these findings, bba62 was downregulated in B. burgdorferi by RpoS in our study, even under in vitro culture conditions.…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
“…Plasmid lp54 has been implicated as being important for the survival of B. burgdorferi in both tick and mammalian hosts, largely because of the presence of the ospAB and dbpBA operons (Caimano et al, 2005;Hagman et al, 1998;Neelakanta et al, 2007;Shi et al, 2008;Yang et al, 2004). Many other genes encoded on lp54 have been found to be differentially regulated in response to temperature, pH and other mammalian-derived signals, which are presumed to be mediated, at least in part, by RpoS (Caimano et al, 2005;Clifton et al, 2006;Ojaimi et al, 2003;Revel et al, 2002). Consistent with these previous findings, our data provided further evidence that 22 lp54-encoded genes are regulated by RpoS.…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%
See 2 more Smart Citations
“…RpoS induces expression of temperature inducible Biological aspects of Lyme disease spirochetes: Unique bacteria of the Borrelia burgdorferi species group genes, like OspC, OspF and DbpA. In contrast, expression of OspA is dependent on housekeeping factor RpoD (σ 70 ) and is downregulated by the RpoS dependent pathway [132][133][134] .…”
Section: Regulation Of Expressionmentioning
confidence: 99%